Virtual reality guided focused Sylvian approach for clipping unruptured middle cerebral artery aneurysms - Zhang, Rui; Hänggi, Daniel; Köskemeier, Pia; Muhammad, Sajjad (Frontiers in Surgery, 2024)
The increasing prevalence of unruptured intracranial aneurysms, detected through advanced brain imaging, necessitates a cautious approach to surgical intervention, with a focus on minimizing associated risks. This retrospective study explores the safety and better aesthetic outcomes of a Virtual Reality (VR) guided Focused Sylvian Approach (FSA) in comparison to the standard Pterional Surgical Approach (SPA) for the clipping of unruptured small-medium-size (<10mm) Middle Cerebral Artery (MCA) aneurysms.23 patients with 23 unruptured MCA aneurysms underwent the VR-guided FSA from June 2020 to September 2023, while 22 patients with 23 unruptured MCA aneurysms who underwent SPA were retrospectively recruited from the medical records database from January 2017 to May 2020. The comparative analysis involved surgical duration, postoperative complications, hospital stay, and a three-month follow-up patient's sequela survey. All aneurysms were effectively treated. The FSA procedure demonstrated a shorter surgical duration compared to the SPA group (164±48 minutes vs. 196±133 minutes, P = 0.2974). Despite a slightly higher median age in the FSA group (59 vs. 56 years), the median hospital stay was shorter in the FSA group (6 days) compared to the SPA group (7 days). The SPA group exhibited a higher incidence of complications (17/23) including cephalalgia, scar irritation, scar numbness, and temporal muscle dysfunction, compared to the FSA group (1/23), with a statistical significance of P < 0.05. Although FSA can not demonstrate significant surgical efficiency in surgical duration and hospitalization, its superior aesthetics and preservation of temporalis muscle function compared to the SPA group. The VR-guided FSA offers improved aesthetics and preservation of muscle function compared to the SPA. Our retrospective study underscores the potential benefits of VR-guided, personalized, focused Sylvian approaches for managing unruptured small-medium-size MCA aneurysms.